2022
DOI: 10.1155/2022/1640193
|View full text |Cite|
|
Sign up to set email alerts
|

Unani Formulation Habb-e-Suranjan: A Treasure of Biological Activities

Abstract: Habb-e-Suranjan (HES), an Unani formulation, has been studied for its anti-inflammatory properties in both in vitro and in vivo experiments. HES is recommended for arthritis, gout, and joint pain. The current endeavor is an attempt to put it to the test and verify its efficacy scientifically. It was tested for DPPH, hydroxyl, and nitric oxide scavenging activities. It was shown that HES had the greatest TAC and FRAC values when compared to catechin and ascorbic acid. HES exhibited DPPH and hydroxyl radical sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%